Modified Maimendong Decoction Inhibits Lung Cancer Metastasis by Up-Regulating Levels of NK and CD8+ T Cells in Peripheral Blood and Tumor Microenvironment - Zhipeng ZHANG; Jianhui TIAN; Zujun QUE; Ziqi CHEN; Bin LUO; Shihui LIU (Zhongliu Fangzhi Yanjiu)
ObjectiveTo explore the mechanism of modified maimendong decoction (MMD) in inhibiting lung cancer metastasis from the perspective of immune regulation. MethodsCTC-TJH-01 and LLC cells were intervened with different concentrations of modified maimendong decoction. The cell proliferation was detected with a CCK-8 kit, apoptosis was detected with an Annexin V-FITC/PI kit, and cell migration was detected through Transwell assays. A lung metastasis model was established through the tail vein injection of LLC cells into C57BL/6 mice, and body weight change and lung tumor metastasis in the mice were evaluated after continuous gavage intervention with MMD. HE staining, immunohistochemistry, and immunofluorescence were employed to observe the histomorphology, Ki-67 protein level, and NK and T cell levels of metastatic lesions. The levels of NK and T cells in the peripheral blood of mice were detected throughflow cytometry. ResultsMMD had no significant inhibitory effect on the proliferation, apoptosis, and migration of CTC-TJH-01 and LLC cells in vitro. In mice, MMD could significantly inhibit the lung metastasis of LLC cells, increase the proportion of NK and CD8+ T cells in peripheral blood and tumor microenvironment (P<0.05), and reduce the expression of Ki-67 protein in metastatic tumor tissues (P<0.05). ConclusionMMD may inhibit the growth of metastatic tumors by upregulating the expression levels of NK and CD8+ T cells in peripheral blood to promote the elimination of circulating tumor cells, and regulating the infiltration of NK and CD8+ T cells in the immune microenvironment of metastatic tumors, then play an antimetastatic role in lung cancer.